12(t-2)+3t=5(3t+5)-8

Simple and best practice solution for 12(t-2)+3t=5(3t+5)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(t-2)+3t=5(3t+5)-8 equation:


Simplifying
12(t + -2) + 3t = 5(3t + 5) + -8

Reorder the terms:
12(-2 + t) + 3t = 5(3t + 5) + -8
(-2 * 12 + t * 12) + 3t = 5(3t + 5) + -8
(-24 + 12t) + 3t = 5(3t + 5) + -8

Combine like terms: 12t + 3t = 15t
-24 + 15t = 5(3t + 5) + -8

Reorder the terms:
-24 + 15t = 5(5 + 3t) + -8
-24 + 15t = (5 * 5 + 3t * 5) + -8
-24 + 15t = (25 + 15t) + -8

Reorder the terms:
-24 + 15t = 25 + -8 + 15t

Combine like terms: 25 + -8 = 17
-24 + 15t = 17 + 15t

Add '-15t' to each side of the equation.
-24 + 15t + -15t = 17 + 15t + -15t

Combine like terms: 15t + -15t = 0
-24 + 0 = 17 + 15t + -15t
-24 = 17 + 15t + -15t

Combine like terms: 15t + -15t = 0
-24 = 17 + 0
-24 = 17

Solving
-24 = 17

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (x+7)(x-1)=(x+2)(x+2) | | -x-x+5x-3=3x+5 | | -(5/9)x=2 | | -10a+3(8+8r)=24+r | | .2x+3.5=16.1 | | 2(2x-1)=26 | | 0.25y-0.01x=0.005 | | y=12-9 | | 6(3.14)=w-6(3.14) | | ((x-1)/3)-2=((x-5)/4) | | 2x+18y=18 | | 3x-11=2x+33 | | 14-b=8 | | -4+3x=7x+x+14x-8x | | 65=-6-x | | 81=x+181 | | 6/10-2/100 | | V-10=-19 | | -4+3x=7x+x+14-8x | | 9a-6=8a+1 | | 2x+2x+x+3x+3=24 | | 2x+0=5y-0 | | 5x+6=9x+3+8x | | 7bf^4-7bk^4= | | 6u(-5u^4)=0 | | 2a-1=3(a+1)+7a+5 | | X+4+5x+3+4x=21 | | (y^-1/4)^1/6 | | 9-3v=0 | | 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) |

Equations solver categories